PREVALENCE OF SUBJECTIVE COGNITIVE DECLINE (SCD) AND THE ASSOCIATION OF MOVING TO SHELTERED HOUSING. (11th November 2018) - Sköldunger, A; Wimo, A; Sjögren, K; Sandman, P; Balash, L; Winblad, B; Edvardsson, D
Abstract: Background A new form of housing has emerged for older people in Sweden, sheltered housing, providing social possibilities for older people feeling anxious, or lonely but otherwise capable of independent living. It is expected that sheltered housing will increase the wellbeing of residents by enhancing social interaction and reducing anxiety. Currently, there are no studies of sheltered housing in Sweden or on the prevalence of subjective cognitive decline among residents in this new form of housing. Aim To examine prevalence of subjective cognitive decline and the association of moving to sheltered housing in Sweden. Methods A cross sectional survey study with cases and controls (n=3805) matched on age, gender and municipality. Results Initial analyses show lower self-rated health and lower functional status in those living in sheltered housing compared to aging in place. A higher proportion of people in sheltered housing report subjective cognitive decline, however there is no strong association of moving to sheltered housing. Conclusion Subjective cognitive decline is more prevalent in sheltered housing compared to ageing in place. This difference indicates a need for longitudinal follow up on trajectories of cognitive decline, resource use and functional capacity of people living in sheltered housing.